Diabetic Neuropathy Clinical Management - Veves, Aristidis; Malik, Rayaz A. (Clinical Diabetes, 2007)
In this newly updated, second edition, leading medical specialists critically review for the general practitioner the latest techniques for the clinical management of diabetic neuropathy. These authoritative contributors focus on the practical aspects of diabetic neuropathy and describe in detail the treatments that are currently available or expected to become available in the near future. They also include concise discussions of the pathogenesis of diabetic neuropathy and highlight the relatively unknown features of neuropathy that can significantly impact a patient's life. Comprehensive, up-to-date bibliographies at the end of each chapter provide an opportunity for the interested physician to gain a more detailed picture of a particular topic.